MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN METODE INKUIRI DI SD - JASWATI, REFLI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Based on facts and conditions in the ground of learning outcomes IPA in class IV SDN 16 Taruko kec.Lintau kab.Tanah Datar less satisfy, because still many students not yet mastered the competencies that should be ownd. This research aimed to describe the plan implementation of learning and increasing yield learning IPA with method incuiri of result research visible that by using the method incuiri can improve result learning IPA students class IV SDN 16 Taruko kec.Lintau Buo Kab.Tanah Datar. Kata kunci :  hasil belajar, pembelajaran IPA, metode inkuiri.